The Architecture of Marcus Vitruvius Pollio In Ten Books - Vitruvius Pollio, Marcus (Cambridge Library Collection - Art and Architecture, 1826)
Active in the first century BCE, Marcus Vitruvius Pollio wrote his influential architectural treatise in ten books. It remained the standard manual for architects into the medieval period. The topics which Vitruvius considered essential are diverse, including aspects of design as well as geometry and engineering. In the nineteenth century, the English architect and author Joseph Gwilt (1784–1863) won greater acclaim for the books he published than for the buildings he designed. His most celebrated achievement, The Encyclopaedia of Architecture (1842), is also reissued in this series. Gwilt's one-volume translation of Vitruvius's Latin text was first published in 1826. Supplanting previous versions, this work was long regarded as the standard edition in English. It contains a brief life of Vitruvius as well as an annotated list of previous editions since the fifteenth century. A number of detailed illustrative plates accompany the text